Earliest Aramaic Inscription Uncovered in Syria. Statue of Newly Discovered King. Bears 10th Century B.C. Bilingual Inscription - Mikaya, Adam
pseudonym; Haddayiš'i of Guzanu and Sapanu; Aramaic-Akkadian